Radiological protection. Minimum criteria for electron paramagnetic resonance (EPR) spectroscopy for retrospective dosimetry of ionizing radiation. ex vivo human tooth enamel dosimetry Part 2, (13th March 2023) - British Standards Institution,
No abstract available